Implementation of the Principle of Restorative Justice as an Alternative Resolving to Types of Crimes in the Related Criminal System Corruption Crimes in Indonesia - Wawan Fransisco (IHSA Institute, 2022)
Restorative justice is basically a criminal law approach that contains a number of traditional values. It is based on two indicators, namely the values ??on which it is based and the mechanisms it offers. This is the basis for considering why the existence of restorative justice is reckoned with.Restorative justiceais a process in which all parties with an interest in a particular violation meet together to resolve jointly to resolve together how to resolve the consequences of the violation for the benefit of the future. From this definition, it can be concluded that the settlement of a criminal act by using Restorative Justice prioritizes the occurrence of an agreement between the litigants, with the interests of the future. Restorative Justice was also introduced because the current criminal justice and criminal justice system created problems. In the current prison system, the purpose of punishment is deterrence, revenge, and suffering as a consequence of his actions. Sentence indicators are measured by the extent to which inmates (prisoners) are subject to prison regulations. more approach to security (security approach).The existence of this approach is perhaps as old as criminal law itself. In addition to imprisonment that has consequences for the families of prisoners, the current system is considered not to relieve or cure victims.Types of crimes that have been resolved through restorative justice are cases of persecution, domestic violence, arson, theft, and murder.The purpose of this research is to find out howImplementation of the Application of Restorative Justice Principles as an Alternative Solution to Types of Corruption Crimes in Indonesia and whether corruption cases can be resolved through the principle of restorative justice.This paper uses a normative legal writing method because it examines laws and regulations, literature, and papers related to the material being studied, which consists of the type of data obtained in this study is secondary data, namely data obtained from library research and documentation, which is the result of research and processing of others, which is already available in the form of literature or documentation.